Undergraduate Students’ Cognizance of Technologies for Self-Regulated Learning - Olumorin Charles Olubode; Onojah Adenike Aderogba; Onojah Amos Ochayi (Indonesian Journal Of Educational Research and Review, 2022)
Self-regulated learning (SRL) is a learning strategy that is guided by metacognition, strategic action and motivation to learn. But its awareness is low. This study therefore investigate undergraduate students’ awareness of technologies for Self Regulated Learning and the influence of gender, level and propreitorship on the cognizance. This study adopted the descriptive design of quantitative survey type. The sample comprised 389 respondents. Data collected were analyzed and tested using mean, t-test and ANOVA while Scheffe’s post-hoc was used to indicate the direction of significant differences at 0.05significant level. The findings established that undergraduate students were aware that Blogs, Facebook, Bookmarks and Wikis are technologies for SRL. There was no difference in undergraduate students’ awareness of technologies for SRL based on students’ academic level. There was significant difference between undergraduate students’ awareness of technologies for SRL based on gender(p=0.001), & school proprietorship(p=0.001). The study concluded that undergraduate students are aware of SRL. This implies that students could be encouraged to utilize technologies for SRL if they are aware of its’ usefulness. It was recommended that Students in seminars should be organized to students on technologies for SRL in their learning process.